TI_GERICHTE 36.2017.93 vom 2. Februar 2018 , RIPAM 2017. Decisione su reclamo. Ricorso tardivo e comunque infondato nel merito - TI Tribunale d'appello (2018)
RIPAM 2017. Decisione su reclamo. Ricorso tardivo e comunque infondato nel merito